Affective and cortical EEG gamma responses to emotional movies in women with high vs low traits of empathy. (October 2019) - Maffei, Antonio; Spironelli, Chiara; Angrilli, Alessandro
Abstract: The present study sought to investigate how differences in trait empathy can influence emotional reactivity to a specific set of affective categories. Forty-one female students, divided in High (HE, n = 20) and Low (LE, n = 21) trait empathy, watched eight validated movie clips divided in four emotional categories (Erotic, Fear, Compassion and Neutral) while subjective evaluation of emotion and EEG gamma activity were recorded. Analysis of self-reports revealed that HE compared to LE exhibited an increased arousal level to all emotional clips. Concerning EEG data, the HE group showed a greater cortical gamma to all the emotional categories compared to the Neutral, while the LE group had greater response only to the negative clips. Participants in the HE group also showed a strong positive correlation between subjective arousal and cortical activity in response to Fear and Compassion clips. The greatest correlation was found to Compassion clips and was located in the right inferior parietal lobe ( r (18)  = 0.63), an important hub for both sensory-emotion integration and empathic sharing of others' emotions. Results suggest that high empathy was associated with enhanced gamma activity and greater self-reported arousal to all emotional stimuli. Furthermore, in this group, scenes with crying characters prompted a distinctive and localized cortical processing. Highlights: Two groups of women with low (LE) vs high empathy (HE) were selected from community. EEG gamma band was measured during the presentation of eight clips of four emotions. The validated film clips fell in the categories: Erotic, Neutral, Compassion, Fear. The HE group showed greater arousal and gamma activity to three emotions, not neutral. In the HE group Gamma was correlated with self-reported arousal of Compassion clips.